Engineering Vascular Self‐Assembly by Controlled 3D‐Printed Cell Placement. (2nd November 2022) - Orellano, Isabel; Thomas, Alexander; Herrera, Aaron; Brauer, Erik; Wulsten, Dag; Petersen, Ansgar; Kloke, Lutz; Duda, Georg N.
Abstract: Nutrient supply via a functional vasculature is essential during regenerative processes, tissue growth, and homeostasis. 3D bioprinting offers the opportunity to engineer vascularized constructs by combining cells and biocompatible materials in specifically designed fashions. However, the complexity of microvascular dynamic networks can hardly be recapitulated yet, even by sophisticated 3D manufacturing. Ideally, the natural organizational competences of endothelial cells will be harnessed such that engineered vascular networks self‐assemble to form complex, controllable microvascular patterns. Here, a bioengineering approach is presented to control microvascular structure formation and to steer cellular self‐assembly of endothelial and supporting cells within a multi‐material stereolithographic 3D bioprinting concept. Bioengineered vascularized constructs are generated by controlled cell deposition in an enzymatically degradable or a non‐degradable material. In vitro, the microvascular structures are regulated in distribution, network orientation, vessel length and branching behavior and developed lumen, signs of vascular stabilization and an interconnected vascular network including anastomosis. This novel biofabrication approach demonstrates the capability to control microvascular network formation by using cellular and spatial cues allowing the generation of distinctly yet precisely vascularized constructs. Such novel approach of controlled microvascular formation may play a fundamental role in the development of vascularized implants or in vitro screening models. Abstract : A multi‐material bioprinting approach is used to engineer vascularized constructs with controllable, self‐assembling microvascular networks. By varying cell placement, supporting cell type and dosage, the microvascular patterns are controllable in shape, orientation, length, and branching behavior. The evolving microvascular networks display lumens, sophisticated interconnections, and other signs of maturation.